PENINGKATAN HASIL BELAJAR TEMA 9 MELALUI MODEL FLIPPED CLASSROOM BERBANTU MEDIA AUDIOVISUAL PADA PESERTA DIDIK KELAS V SDN 1 MARGOYOSO - Bayu Setya Abrori; Aryo Andri Nugroho; Tri Sugiyono (JURNAL HANDAYANI PGSD FIP UNIMED, 2021)
Abstract: During the pandemic, the learning outcomes of students in class V at SDN 1 Margoyoso were quite low. This can be seen from the average value of the class which is 61.5. While the number of students who passed the KKM was 5 people. This study aims to describe efforts to improve learning outcomes for theme 9 through the flipped classroom learning model assisted by audiovisual media in class V at SDN 1 Margoyoso. The flipped classroom learning model assisted by audiovisual media is a learning model that uses two syntaxes, namely synchronous and asynchronous, and is assisted by the use of audiovisual media in the form of video learning materials. Learning themes through the flipped classroom model is effective in improving student learning outcomes. Learning outcomes in learning through the flipped classroom model, in the first cycle the average class learning outcomes of students reached 43.45 with the number of students passing the KKM 20% of all students to an average class learning outcome of 78.6 with the number of students passing the KKM 85% . The conclusion of the learning outcomes shows that learning themes through the flipped classroom learning model assisted by audiovisual media can improve student learning outcomes. Keywords: Learning Outcomes, flipped classroom, audiovisual.Abstrak: Pada masa pandemi, hasil belajar peserta didik di kelas V SDN 1 Margoyoso cukup rendah. Hal ini nampak dari nilai rata-rata kelas yakni 61,5. Sedangkan jumlah peserta didik yang lolos KKM adalah 5 orang. Penelitian ini bertujuan untuk mendeskripsikan upaya meningkatkan hasil belajar tema 9 melalui Model pembelajaran flipped classroom berbantu media audiovisual di kelas V di SDN 1 Margoyoso. Model pembelajaran flipped classroom berbantu media audiovisual ialah model pembelajaran yang menggunakan dua sintaks yakni synchronous dan asynchronous, serta dibantu dengan penggunaan media audiovisual berupa video materi pembelajaran. Pembelajaran tema melalui model flipped classroom efektif dalam meningkatkan hasil belajar peserta didik. Hasil belajar dalam pembelajaran melalui model flipped classroom, pada siklus pertama rata-rata hasil belajar kelas peserta didik mencapai 43.45 dengan jumlah peserta didik lolos KKM 20% dari keseluruhan peserta didik menjadi rata-rata hasil belajar kelas 78.6 dengan jumlah peserta didik lolos KKM 85%. Simpulan hasil pembelajaran menunjukan bahwa pembelajaran tema melalui model pembelajaran flipped classroom berbantu media audiovisual dapat meningkatkan hasil belajar peserta didik.  Kata kunci: Hasil Belajar, flipped classroom, audiovisual.